Service Quality an Antecedent of Customer Satisfaction - Dr. Hassan Raza (International Journal of Experiential Learning & Case Studies, 2024)
The study is conducted on customers of banks in Pakistan to find out whether service quality is an antecedent of customer satisfaction. The study also provides the comparative analysis of four alternative extended versions of service quality models namely SERVQUAL, Weighted SERVQUAL, SERVPERF, and Weighted SERVPERF. The quantitative analysis has been conducted and to form the sample for the study, self-administered questionnaires have been distributed and responded to by 500 customers of Pakistani commercial banks. The data was analyzed on four alternative service quality models concerning customers’ opinions regarding service quality expectations, perceptions, and importance, and their impact on customer satisfaction and further efficacy of these alternative models have been compared. The comparative analysis of four alternative service quality models has been carried out by applying construct validity, reliability, uni-dimensionality, and model fit indices on service quality variables revealing that all four service quality models fulfilled the requirement of validity, reliability, and goodness of fit as well as the models significantly and positively impact the customer satisfaction, however, the superiority and higher effectiveness of the Weighted SERVPERF model over the other three service quality models have been established. The mean-based ranking of four alternative service quality models has been attempted and further analysis of banks' high and low-performing variables from a customer perspective was performed. In the Weighted SERVPERF model, the tangible, reliability, and responsiveness variables were established as high-performing, whereas empathy and assurance variables were established as low-performing variables. The bank management should enhance customer satisfaction by improving service quality with a more focused approach as provided in this study.